FEATURES OF THE COURSE OF PREGNANCY IN PATIENTS WITH CONNECTIVE TISSUE DYSPLASIA - Yunusova Z. M. (Web of Journals Publishing, 2024)
The article is devoted to the problems associated with connective tissue dysplasia (CTD), predominantly undifferentiated forms of the disease (nDST). The relevance of the topic is due to the high prevalence of this pathological condition. The generalized nature of connective tissue damage with the involvement of the reproductive system in the pathological process significantly affects the course of pregnancy and Birth. Complications that may be associated with pregnancy, childbirth and the postpartum period in women with nDST and which cause a high need for surgical aids: amnio-, episio- and perineotomy, cesarean section are presented. Particular attention is paid to magnesium, which plays one of the determining roles in the complex biosynthesis of the extracellular matrix in the formation of connective tissue and in the morphofunctional state of fibroblasts. The methods used to detect connective tissue metabolism disorders (determination of the level of oxyproline and fibronectin in blood serum, pyrinx D and glucosaminoglycans in urine, etc.) are described. In view of the lack of reliable diagnostic (biochemical and genetic) criteria for nDST, special attention is paid to the need for an integrated approach to assessing the condition of patients using anamnesis data, the results of clinical, instrumental and laboratory examinations.
Keywords: connective tissue dysplasia, hemostasis, complications of pregnancy and childbirth, magnesium deficiency, endothelial dysfunction, markers of collagen breakdown, genital prolapse.